Studi Penggunaan Balok Lintel Pada Bangunan Gedung Infilled Frame 2 Lantai Menggunakan SAP2000 - Petrus Tobi Tukan; Partogi H Simatupang; Elia Hunggurami (Universitas Nusa Cendana, 2021)
The two stories building construction or which is commonly called the two stories building these days is very popular in Indonesia. The type of multistories building technology that develop in the world of construction is very diverse, this development is can not be separated from the anticipation of the various of loading conditions. Based on that facts, the research of the use of lintel beams in 2 stories infilled frame buildings is conducted. The analysis can be done by using SAP2000 software. The structure model analyzed by comparing the structure responses between the building that use the lintel beams system and the other one is the building that don’t use that system, where as the idealized loading is same. The result of the analysis obtained by using the lintel beams system the value of maximum x and y axis base shear respectively are 344,088 KN and 363,001 KN, the maximum column moment is occurred in column 84 with the value is 99,58 kNm, and the maximum x axis lateral drift is occurred in joint 128 with the value is 0.000401 m, while the y axis is occurred in joint 105, 128 with the value is 0,000533 m. The analysis result that obtained for the building that don’t use the lintel beam system, the x and y axis maximum base shear value respectively is 336,425 KN and 354,539 KN, the maximum column moment occurs in column 84 is 98,98 kNm, and the x axis maximum drift lateral occurs in joint 128 with value is 0,000406, while the y axis maximum lateral drift occurs in joint 105, 128 with value is 0,000532. So we obtained the percentage comparison on base shear value between 2 stories infilled frame building that use lintel beams system and the building that doesn’t use the lintel beams system for x axis is 1,45% and y axis is 1,13% , and for the percentage comparison on maximum column moment value is 0,30% , while the percentage comparison on drift lateral value for x axis is 0,62% and y axis is 0,09%